2008
DOI: 10.1902/jop.2008.070479
|View full text |Cite
|
Sign up to set email alerts
|

Subepithelial Connective Tissue Graft for Root Coverage in Smokers and Non‐Smokers: A Clinical and Histologic Controlled Study in Humans

Abstract: Root coverage with subepithelial connective tissue graft was negatively affected by smoking, which limited and jeopardized treatment results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 42 publications
0
40
2
6
Order By: Relevance
“…These data are alarming for the daily practice because smokers might not be entirely satisfied with the aesthetic improvement through a small reduction in gingival recession and such a low predictability for full root coverage procedure. The damage caused by smoking seems to have been intense enough to make the majority of smoking patients of the present study yield a root coverage of less than 50% (67.5% of the cases), while for Souza et al (15) the majority of smokers presented root coverage between 50% and 99% (60% of the cases).…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…These data are alarming for the daily practice because smokers might not be entirely satisfied with the aesthetic improvement through a small reduction in gingival recession and such a low predictability for full root coverage procedure. The damage caused by smoking seems to have been intense enough to make the majority of smoking patients of the present study yield a root coverage of less than 50% (67.5% of the cases), while for Souza et al (15) the majority of smokers presented root coverage between 50% and 99% (60% of the cases).…”
Section: Discussioncontrasting
confidence: 50%
“…After 6 months, this had occurred in only 2 cases (5% of the treated cases -data not show), both in TG, without statistically significant difference from CG. Souza et al (15) reported full root coverage in 6.7% of the cases, while Erley et al (14) obtained 25% and Andia et al (11) obtained none. These data are alarming for the daily practice because smokers might not be entirely satisfied with the aesthetic improvement through a small reduction in gingival recession and such a low predictability for full root coverage procedure.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations